A Conceptual Critique of Asia Versus the West - Mazdak Rajabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“Asia Versus the West” is still one of the most important books concerning the historical understanding of the East as a basic source of human civilization in comparison with the West. The book commences from the point which has not hitherto been considered, except for Ahmad Fardid, who has invented the term “Westernized” by which he explains the relation of “us” and the West, but his lectures had not been published before Shayegan wrote his book. Shayegan states the westernized situation as “double nihilism” to which we should pay attention in order to think of the West as our fundamental problem. I review the book in addition to its most important theme, which is nihilism.